Complete mitochondrial genome of Sicyopterus japonicus (Perciformes, Gobiidae). (June 2013) - Chiang, Tzen-Yuh; Chen, I-Shiung; Lin, Hung-Du; Chang, Wen-Been; Ju, Yu-Min
<x xml:space="preserve">Abstract</x> In this study, we sequenced the complete mitochondrial genome of Sicyopterus japonicus (Perciformes, Gobiidae). This mitochondrial genome consists of 16, 514 base pairs (bp), with 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and 1 non-coding control region (CR), also with the gene synteny identical to that of typical vertebrates. CR, of 843 bp in length, is located between tRNAPro and tRNAPhe. The overall base composition of the heavy strand shows T 26.1%, C 28.7%, A 28.3%, and G 16.91%, with a slight AT bias of 54.4%.